Prompt gamma activation analysis on volcanic rocks from the Balaton-Highland to North-Patagonia - Gméling, Katalin (2009)
The importance of the light elements in geochemistry has been growing because the analytical techniques for measuring them went through a great improvement. Boron is an incompatible and fluid-mobile element possessing two isotopes with greatly different abundances in nature, and also the abundance of boron greatly differs in different reservoirs. These facts make boron an important tracer of the recycled materials is subduction zones. In the subducting slab most of the boron is concentrated in the oceanic crust and sediments, but most of it leaves the slab close to the suture zone of the subduction. However, some minerals can retain boron and carry it further down into the mantle, even reaching depths of the lower mantle and taking part in deep recycling. The most suitable analytical techniques for B concentration measurements, is a non-destructive nuclear method of prompt gamma activation analysis (PGAA). This article resumes conclusions based on the B data measured in volcanic rocks from a back-arc basin setting from the Balaton-Highland and North-Patagonia. We emphasize that the origin of the alkaline basalt magmas in these regions are connected to extension influenced decompression-melting and asthenospheric upwelling. The B/Sm ratio of the examined rocks from Balaton-Highland and Crater Basalt volcanic fields overlap and are higher than those from Rio Genoa. The greater amount of fluid-mobile boron in the alkaline basalts from the Balaton-Highland compared to the North-Patagonian samples, indicate higher value of crustal thinning due to extension in the Pannonian basin.